THE DIFFERENCE EFFECT BETWEEN ORAL AND PARENTERAL IRON SUPPLEMENTATION ON BODY WEIGHTS OF THE INFANT OF ANEMIC PREGNANT WISTAR RAT (RATTUS NORVEGICUSS) - Noviyanti, Retno Dewi (JURNAL PROFESI || MEDIA PUBLIKASI PENELITIAN, 2014)
Iron deficiency anemia during pregnancy can increase the risks of low birth weight infant, premature birth, and impaired fetal growth. The objective of this research is to investigate the difference effect between oral and parenteral iron supplementation on body weights of the infant of anemic pregnant rat. This research used the experimental laboratory research method with the randomized controlled trial design. Thirty rats were divided into three groups and each group consisted of 10 rats. Group I was given an oral iron supplementation, group II was given parenteral iron supplementation, and group III as control group was not given any of such supplementations. This research was conducted until the mother rat gave birth, observed was body weights all of the infant rats with digital scales. The data of the research were analyzed by using Kruskal Wallis then Mann Whitney formula. The results of Kruskal Wallis that the comparisons of the average of groups I, II, and III for body weights of the infant are 6.09±0.40 g: 6.59±0.49 g: 5.81±0.39 g (p<0.001), the results of Mann Whitney that there are a difference body weights of the infant (p<0.001) between oral and parenteral iron suplementation. Based on the results of the research a conclusion is drawn that there is a difference in the body weights of the infant between oral and parenteral iron supplementation. The average body weights of the infant in the parenteral iron supplementation are better than those in the oral iron supplementation.   Keywords:  Iron supplementation, oral, parenteral, pregnancy, anemic rat, body weights of the infant.